INCREASE OF THE BEARING ABILITY OF THE COLUMNS STRENGTHENED BY INHALINGS - Kh. M. Muselemov; O. M. Ustarkhanov; A. K. Yusupov; I. T. Yarakhmedov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The article considers the behavior of the columns strengthened by horizontal struts in one and two levels. The shafts of the pillars are taken from conventional steel and wood. Sets out the detailed calculation of the columns, graphics are given of the consumption of metal. Conclusions.